Ternary Images of Self-Dual Codes and Cyclic Codes over F3 + vF3 - Lampos, John Mark (Philippine computing journal)
By configuring an adequate set of messages obtained by an adversary and analyzing the information which can be obtained by an adversary, it is possible to verify the secrecy of crptography protocols.